Energetic valorization of municipal solid waste in Morocco: financial feasibility of refuse derived fuel production. Issue 1 (1st October 2022) - Ouigmane, A; Boudouch, O; Hasib, A; Ouhsine, O; Abba, E; Isaifan, R J; Aadraoui, M; Berkani, M
Abstract: The management of municipal solid waste is considered as a problem of municipalities in developing countries due to its impact on the environment and on human health. Energy recovery is considered as a sustainable waste management solution. The objective of this paper is to carry out a financial feasibility study of refused derived fuel (RDF) recovery in a region in Morocco. The results show that the cement plant requires 24, 000 tons of RDF to substitute 15% of the pet coke used to produce 1 million tons of clinker per year. Thus, 14, 000 tons of pet coke will be saved annually in this case. The results of comparing the net present values (NPV) of three investment scenarios show that the project is profitable if the investor is the cement plants or the group of municipalities with a selling price of 36 USD/ton of RDF. On the other hand, if the landfill company is the investor, the project becomes profitable from a sale price of 39USD/ton of RDF.